(untitled) (Journal of Guidance and Counselling Studies, 2025)
This study determined teachers’ self-efficacy as correlate of their occupational stress in public primary school in Agbani Education Zone of Enugu State. Three purpose statements, three research questions guided the study and three null hypotheses were tested at 0.05 level of significance. This study adopted the correlation survey research design. The population of this study consists of 1904 public primary school teachers. The sample of the study comprises of 300 primary school teachers in Agbani Educational zone. Two instruments were used for data collection. They are Self-efficacy Scale (SES) by Sheker, Maddux, Mercadante, Prentice-Dunn, Jacobs and Rogers in 1982. The second instrument is titled Social Anxiety Questionnaire (SAQ- A30) developed by Caballo, Irurfia and CISCO-A Research Team (2010). The instruments were validated and its reliability established. Data was collected by the researcher with the help of Ten research assistants who assisted in the distribution and collection of the instrument. Data collected was analyzed using Pearson Product Moment Correlation (r) and multiple regression analysis. The findings of the study revealed that a moderate positive relationship exists between teachers’ self-efficacy scores and their occupational stress, a very low positive relationship exists between male teachers’ self-efficacy scores and their occupational stress; a very low positive relationship exists between female teachers’ self-efficacy scores and their occupational stress; there is no significant relationship between male teachers’ self-efficacy scores and their occupational stress; there is no significant relationship between female teachers’ self-efficacy scores and their occupational stress; there is a significant relationship between teachers’ self-efficacy scores and their occupational stress scores in public primary school in Agbani Education Zone of Enugu State. The study recommends among others that seminars and workshops should be organized to improve the level of self-efficacy among teachers. Workshops on yoga and meditation for women teachers should be organized to minimize the level of their occupational stress and increase the level of spiritual intelligence and teacher self-efficacy.